Global Corporate Stress Tests-Impact of the COVID-19 Pandemic and Policy Responses - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2021)
Corporate sector vulnerabilities have been a central policy topic since the outset of the COVID-19 pandemic. In this paper, we analyze some 17,000 publicly listed firms in a sample of 24 countries, and assess their ability to withstand shocks induced by the pandemic to their liquidity, viability and solvency. For this purpose, we develop novel multi-factor sensitivity analysis and dynamic scenario-based stress test techniques to assess the impact of shocks on firm's ability to service their debt, and on their liquidity and solvency positions. Applying the October 2020 WEO baseline and adverse scenarios, we find that a large share of publicly-listed firms become vulnerable as a result of the pandemic shock and additional borrowing needs to overcome cash shortfalls are large, while firm behavioral responses and policies substantially help overcome the impact of the shock in the near term. Looking forward, while interest coverage ratios tend to improve over time after the initial shock as earnings recover in line with projected macroeconomic conditions, liquidity needs remain substantial in many firms across countries and across industries, while insolvencies rise over time in specific industries. To inform policy debates, we offer an approach to a triage between viable and unviable firms, and find that the needs for liquidity support of viable firms remain important beyond 2020, and that medium-term debt restructuring needs and liquidations of firms may be substantial in the medium-term.